Reconstructing Islamic Digital Ethics for Generation Z through Syed Ahmad Khan's Tahdzib al-Akhlaq - Muhammad Ihsan Siregar; Malikha Kumala Nabila; Zanuba Naila Firdausa Em.Ha; Eko Suwanto; Muhammad Alawi Sumairi (Journal of Contemporary Islamic Education, 2026)
The rapid expansion of digital technology has transformed the patterns of interaction, communication, and identity formation among Generation Z, while simultaneously generating various ethical challenges, including cyberbullying, misinformation, hate speech, algorithmic manipulation, and the misuse of artificial intelligence. Existing approaches to digital ethics primarily emphasize digital literacy and technological competence, yet they often overlook the moral, social, and spiritual dimensions of human behavior. This study aims to analyze the moral foundations of Syed Ahmad Khan’s Tahdzib al-Akhlaq, examine its relevance to the ethical challenges faced by Generation Z in digital environments, and reconstruct an Islamic digital ethics model suitable for contemporary society. Employing a library research method, this study utilizes historical, philosophical, and critical approaches to analyze Tahdzib al-Akhlaq alongside contemporary literature on digital ethics, artificial intelligence, and Islamic education. The findings demonstrate that the moral philosophy articulated in Tahdzib al-Akhlaq remains highly relevant for addressing ethical dilemmas arising from digital transformation. Through a systematic conceptual reconstruction, the study identifies four interrelated dimensions Rational Digitality, Moral Responsibility, Social Accountability, and Spiritual Awareness, which collectively constitute the Tahdzib al-Akhlaq Digital Ethics Model (TADEM). This study contributes to contemporary Islamic educational theory by positioning TADEM as a conceptual framework that bridges classical Islamic moral philosophy with contemporary digital ethics. The model extends existing digital ethics frameworks by integrating rational, moral, social, and spiritual dimensions, thereby offering a holistic approach to cultivating ethically responsible digital citizens in the age of artificial intelligence.